Scenario Praxis for Systemic Governance: A Critical Framework. (August 2014) - Ison, Ray; Grant, Andrea; Bawden, Richard
Scenario praxis, critically explored as the theory-informed practice of scenarioing, is proposed as a modality for institutionalising knowing within a systemic governance framework. Framing and institutional considerations associated with a constructivist inquiry-based learning approach that might open capacity for innovation in future scenarioing praxis are outlined to complement and counterbalance positivistoriented evidence-based approaches. Drawing on espoused theoretical and epistemological commitments, background literature, researcher experience, and our framing choices, we describe a heuristic device for use ex post to critically examine accounts of past scenario development, or ex ante to generate scenarios. The heuristic and its process of generation are designed for use in context-sensitive ways suited to the systemic governance of climate change adaptation and similar situations that can be framed as 'wicked' or uncertain.